Bright red electroluminescence from Al2O3/Eu2O3 nanolaminate films fabricated by atomic layer deposition on silicon. (15th April 2021) - Wang, Yuanyuan; Yu, Zhimin; Yang, Yang; Sun, Jiaming
Abstract: Silicon-based metal-oxide-semiconductor light-emitting devices (MOSLEDs) based on the Al2 O3 /Eu2 O3 nanolaminate films are fabricated by atomic layer deposition, which emit red electroluminescence (EL) peaking at 613 nm with the external quantum efficiency of 5.47% and power efficiency of 0.14%. The EL originates from the impact excitation by hot electrons via Poole-Frenkel mechanism, manifesting a maximum power density of 1.93 mW/cm 2, and the excitation cross section up to 1.09 × 10 −14  cm 2 . A low annealing temperature (650 °C) is preferable to suppress Eu clustering. The critical distance for cross relaxation between dopant layers is derived to be ~2.02 nm. The higher excitation efficiency from these Al2 O3 /Eu2 O3 MOSLEDs is speculated to originate from the higher excitation possibility due to the energy distribution of hot electrons within Al2 O3 matrix that beneficial for photons with lower energies, and the limited competition from non-radiative transitions within Eu 3+ ions. Graphical abstract: Image, graphical abstract